Political Science: Pioneers and Schools - Boudiaf, Mohamed (Journal of Legal Studies and Researches, 2025)
Political science has managed to assert its independence after a historical trajectory marked by fluctuations and intellectual interruptions that questioned its identity. It began to take shape as a distinct discipline, eventually evolving into a comprehensive academic field. This paper seeks to trace this trajectory, considering its prominent pioneers and the institutions. It also examines achievements in the current era.